Urgensi Pemanfaatan Multimedia pada Pendidikan Agama Islam Jenjang SMK - Achmad Setiawan; Asrowi Asrowi; Nunuk Suryani (Teknodika, 2017)
This study aims to provide an overview of the importance and urgency of the use of multimedia to be used in learning Islamic religious education (PAI) courses at the level of vocational high school (SMK). Data on the use of multimedia in various scientific disciplines is obtained through a comprehensive literature study. Furthermore, the data are discussed based on theory and harmonized with the findings of previous research on the benefits of multimedia in the learning process. Furthermore, the analysis of PAI learning objectives shows the element of personal formation which has a noble character to the Creator, fellow human beings and nature. Based on interviews with SMK PAI teachers in Surakarta it was found that PAI subjects were not given much attention in their implementation. This can be seen in the allocation of study hours which is only 2 hours per week with a very broad range of material. Whereas the expected outcomes in the PAI subjects are very important and very useful in the moral formation of the workers in the future. So, it can be concluded that the use of multimedia in the learning of PAI at the Vocational School level is very much needed so that students can learn not only in class but can independently so that the learning objectives of PAI can be achieved